Creative Industries’ Risk Appetite in East Java and Its Impact on Dynamic Capability and Competitive Advantage - Agus Purnomo Sidi; Risa Santoso (Bina Nusantara University, 2024)
Studies related to risk appetite, which plays an important role in risk management in the creative economy sector, still need to be made available, so relating it with dynamic capabilities and competitive advantage is the main novelty of the research. The research aimed to understand the risk appetite of the creative Small and Medium-Sized Enterprises (SMEs) in East Java, Indonesia, and analyze the impact of the risk appetite on their dynamic capabilities and competitive advantages. Primary data was obtained through a quantitative research method with a Likert-sized online questionnaire instrument and distributed to 300 creative industries in East Java, with the unit of analysis being the creative business owner. The data were analyzed using Partial Least Square - Structural Equation Modelling (PLS-SEM) weight analysis with SmartPLS version 4 software. After passing the external test and inner model, hypothesis testing was carried out by reviewing the t-statistics and p-values. The analysis results provide a surprise, showing that not all types of risk appetite significantly impact dynamic capabilities and competitive advantage. Avoiding the discovery of detrimental risks to dynamic capabilities and competitive advantage emphasizes that in this era, every creative SME must face risks. Avoiding risks makes the business unable to face dynamic changes in conditions and will not have a competitive advantage. However, risk and revenue sharing do not significantly impact competitive advantage. It has a strong impact through dynamic capabilities. Creative SMEs can choose to transfer risks or reduce them. Future research can examine different risk appetites for creative economy in each subsector.